POKDARKAMTIBMAS PAMULANG SEBAGAI IMPLEMENTASI KEMITRAAN DALAM KONTEKS COMMUNITY POLICING - Mario Humberto (Jurnal Kriminologi Indonesia, 2011)
Police Decree No. Pol. : SKEP/737/X/2005, explained that the implementation partnership in the community policing context is between the police and FKPM. Through FKPM expected partnership between police and community in the community policing context that can be realized. In the Pamulang Police jurisdiction, found that the role of FKPM not walk, but instead there is one other form of partnership between police and community who called Pokdarkamtibmas Pamulang, which is more active in conducting real activities of crime prevention or security driven and problem solving. Research in this thesis are to understand the position and relationship Pokdarkamtibmas Pamulang with the police and FKPM, and effectiveness Pokdarkamtibmas Pamulang in in partnership with the Police in the context of community policing realize. Primary data in this study is the result of interviews with seven resources persons from various parties, namely Metro Police Pamulang, Kelurahan Pondok Cabe Udik, FKPM, and Pokdarkamtibmas Pamulang. The results of this study showed that Pokdarkamtibmas Pamulang is also FKPM because the elements of the same members as FKPM namely: RT, RW, religious leaders, community leaders, youth leaders. But unfortunately, the formal forms of Pokdarkamtibmas Pamulang limiting community involvement. While community involvement is an important part of community based crime prevention. Also found that Pokdarkamtibmas Pamulang still not appropriate in the context of community policing.